On the scattering behaviour of bullet-rosette and bullet-shaped ice crystals - B. Strauss (Annales Geophysicae, 1996)
The scattering behaviour of bullet-rosette and bullet-shaped ice particles is investigated using model calculations (ray tracing method) with special emphasis on the asymmetry factor g. Because the variability of the geometrical features of these particles is very large, some representative shapes are used in the calculations. The model is based on geometrical optics, and particles are assumed to be oriented randomly; a wavelength of 0.56 μm is considered; absorption is neglected. The scattering behaviour of bullet rosettes is compared to that of single branches out of the bullet rosette. It turns out that there are slight differences in the asymmetry factor values, depending on the lengths of the branches (∆g~0.02) and on the angles between the branches (∆g~0.01). Bullets show some special features in their phase functions due to the pyramid. The length of the particle influences the asymmetry factor (∆g~0.10), as does the shape of the pyramid (∆g~0.07). The influence of the pyramidal shape decreases with increasing particle length. Bullets were compared to hexagonally shaped columns. This was done for two columns, one as long as the columnar part of the bullet (length without pyramid), and one for a column as long as the bullet including the pyramid. Asymmetry factor values of bullets with a pyramidal angle of 28° deviate less than ∆g~0.01 from the range given by the two values of the columns.